ANALISIS BIBLIOMETRI USAHA MIKRO KECIL MENENGAH PADA JURNAL EKONOMI DAN PEMBANGUNAN 2016-2020 - ROCHANI NANI RAHAYU; SENSUSIYATI; SUTARNO; IMAM SUGKAWA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
A bibliometric analysis was conducted on the 2016-2020 Economic and Development Journal. The research objectives are: 1) The number of articles published by the 2016-2020 Economic Development Journal; 2) Authorship pattern; 3) Degree of collaboration; 4) The most prolific writer; 5) Gender of the author; 6) The institution where the author works 7) The most research topics. Data from the Journal of Economics and Development is used which is accessed from https://jurnalekonomi.lipi.go.id/. The data recorded is the number of articles, the name and gender of the author, the institution and the author’s keywords. Furthermore, the data is processed using frequency distribution statistics, then presented in tabular form. The results of this research show that the 2016-2020 Journal of Economics and Development published 54 articles, written by 107 authors (65 males and 42 females). The value of the degree of collaboration is 0.63. The most prolific authors are Endro Gunawan of the Ministry of Agriculture, Center for Socio-Economic and Agricultural Policy and Rima Setiani is a researcher from the Center for Horticulture Research and Development, each of whom wrote 3 articles. The most productive institution is the LIPI Economic Research Center, and the most productive university is Padjadjaran University, Economics Study Program, Faculty of Economics and Business. Universities from abroad also write in the Journal of Economics and Development, namely the National Graduate Institute for Policy Studies, Tokyo Japan. Economics, Planning, and Public Policy Program. The conclusion of the study is that male writers are more dominant than female writers, more articles are written in collaboration than articles written individually, the Journal of Economics and Development is known abroad, and MSMEs are the most research topics.